Fresh water aquaculture fish consumption in Malaysia and heavy metals risk exposure to consumers - Abu Bakar, Ibrahim; Ayob, Mohd Khan; Abdullah Sani, Norrakiah; Zainuddin, Intan Fazleen (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
This study aimed to determine the amount of the fish (Oreachromi sp, Clarias sp. and Pangasius sutchii) consumption in Malaysia; the quantity of heavy metal residues (arsenic, cadmium, mercury and plumbum) in the fish and the level of the risk exposure. About 1440 respondents from six main production districts were randomly interviewed and the body weight of the respondents was also measured. A total of 240 ready to eat fish from food premises were also stratified randomly sampled where each sample was weighted to determine the average weight of one serving unit sold at food premises. The heavy metal residues were analyzed using Inductively Coupled Plasma–Optical Emission Spectrometer (ICP-OES) Optima 4300 DV (German). The level of heavy metals risk exposure was calculated as the percentage value of ’Provisional Tolerable Weekly Intakes’ (PTWI) and recalculated using computer programme @Risk 4.5 Excel (Palisade, USA). The result showed that 60.3% of the respondents consumed the fish. The level of heavy metal risk exposures were calculated as very low i.e. 0.14% (As), 0.31% (Cd), 0.09% (Hg) and 0.78% (Pb).